Perceiving Ben O’kri’s The Famished Road: The Role of Postcolonial Hybridity - Halim, Amira (Journal of Human Sciences, 2021)
Ben O’kri’s The Famished Road is a magical realistic novel that gives credibility to the idea of talking to the dead. A talking dead is not a new concept in the African culture for the child who returns to life in another body is an accepted notion. Being a Nigerian novelist, Ben Okri uses Azoro or Abiku as the main character who lives in reality with his family but originally comes from the immortal world. Depicting this scene, it is believed that Okri is influenced by the Nigerian culture; however, Okri uses this kind of Animist Realism out of a postcolonial indoctrination. Okri relies on the hybridity of the current Nigerian culture to help perceiving the intended political message. Nigerian readers are not required to willingly suspend their disbelief; however, they are asked to use their imagination, resulted from the colonial and the African influence, to conceive the message.